1998
DOI: 10.1111/j.1528-1157.1998.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcomes in Randomized Controlled Trials of Antiepileptic Drugs: A Systematic Review of Methodology and Reporting Standards

Abstract: Summary:Purpose: To systematically review the methodology and use of neuropsychological tests in randomized controlled trials (RCTs) of antiepileptic drugs (AEDs) in patients with epilepsy.Methods: Trial reports were found by searching Medline 1966-1 996 and searching through journals by hand. Inclusion and exclusion criteria were applied, and methodological and neuropsychological test data was extracted by using a proforma.Results: 43 reports met our inclusion criteria, representing 40 RCTs, as three RCTs had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 59 publications
0
22
0
1
Order By: Relevance
“…It is likely that this is associated with a risk of adverse side effects, in particular with respect to central nervous system functions, such as learning or formation of memory, which depend on long‐term excitability change through increases or decreases in synaptic strength. Although a plethora of patients are treated by AEDs, systematic research of such side‐effects and valid interpretation are difficult, and the existing knowledge is largely anecdotal and stems from retrospective studies (Cochrane et al. , 1998; Goldstein, 1998; Kwan & Brodie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this is associated with a risk of adverse side effects, in particular with respect to central nervous system functions, such as learning or formation of memory, which depend on long‐term excitability change through increases or decreases in synaptic strength. Although a plethora of patients are treated by AEDs, systematic research of such side‐effects and valid interpretation are difficult, and the existing knowledge is largely anecdotal and stems from retrospective studies (Cochrane et al. , 1998; Goldstein, 1998; Kwan & Brodie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The RMMT, for example, is sensitive to changes in memory function produced by drug side effects 21 and anorexia nervosa. 22 A number of studies have found the Stroop test and the digit symbol subtest useful in assessing drug side effects, 23 treatment effects 24 and chronic occupational exposure to toxic substances. 25 These tests were also chosen on the basis of their ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…reported the methodological problems in these studies affecting interpretation and assessed the consistency, reliability, and validity of neuropsychological tests used in research on the cognitive effects of AEDs in people with epilepsy (33).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%